Hábitos alimentares de crianças de um ano a dois anos de idade Belém-Pa - PIRES, Izabella Pessoa de Lima (2023)
This work aims to characterize the eating habits of children between one year and two years old in the city of Belémpa. In addition, secondary secondary was the relation between the sociodemographic data of mothers and/or caregivers with the offer of food to children under two years of age; as well as describe the complications and relate to healthy eating habits. The study was conducted through a questionnaire via the Internet, using the Google Form platform, after approval by the ethics committee. After the results, it was possible to observe that the marital status and level of education have an influence on the feeding of infants, as well as children who breast fed get sick less, as well as the use of artificial teats is still present in children from Belize. Therefore, it was extremely important to carry out this study for the academic community since there is little research involving the city of BelémPA.